Persepsi Guru Sekolah Dasar terhadap Penggunaan Media Angklung dalam Pembelajaran Seni Musik - Aninnafidz Ahmad Naufal; Resa Respati; Anggit Merliana (JURNAL ARMADA PENDIDIKAN, 2025)
Music education in elementary schools emphasizes the development of students' personalities through contextual and meaningful musical experiences. One way to provide meaningful musical experiences is through the use of instructional media, such as the angklung. This study aims to examine elementary school teachers' perceptions of the use of angklung as a learning medium in music education. The study employs a quantitative approach using a descriptive survey method. A total of 123 elementary school teachers in Cidahu District, Kuningan Regency, were selected as the sample. Data were collected using a questionnaire instrument, and the data analysis technique used was descriptive analysis. The results of the study indicate that the majority of teachers' perceptions fall into the good category (70%), while a smaller portion fall into the fairly good category (30%). This suggests that teachers possess positive knowledge, feelings, attitudes, judgments, habits, and tendencies toward the use of angklung as an instructional medium. Based on these findings, it is recommended that training and mentoring be provided to teachers to enhance their understanding and implementation of angklung as a medium for teaching music in elementary schools.